Homsy’s sign in DTPA renogram- initial experience at NINMAS - Alam, Sumaiya; Parveen, Rahima; Reza, Sharmin; Sultana, Saleha; Islam, Urnas; Bailey, Shamsun Nahar; Parveen, Rumana; Akter, Fahmoda; Islam, Md Saiful; Sultana, Nasreen (Bangladesh Journal of Nuclear Medicine, 2024)
Introduction: Renogram findings in intermittent hydronephrosis may occur as a delayed double peak curve and can be considered as a possible fourth drainage pattern. It usually occurs 10.15 min post-diuretic injection and presents with an initially rapid tracer elimination followed by a sudden cessation of the effect or reversion to a rising curve resulting from self-obstruction of the pelviureteric junction (PUJ) by forced diuretics. This type of response is known as Homsy.s sign and is an indicator of an intermittent PUJ obstruction (PUJO). Objective: Patients with Homsy.s syndrome may easily be mistaken, and eventually an obstructive pattern is missed if the proper duration of the study is not carried out. The purpose of this study is to find out whether these are true obstructive patterns, with particular emphasis on the characteristic clinical and imaging findings in intermittent PUJO. Patients and methods: A retrospective study was conducted at NINMAS from October 2023 to January 2024 at the scintigraphy division of the National Institute of Nuclear Medicine and Allied Sciences. A total of eight patients with Homsy.s sign characteristics in a DTPA renogram with diuretic challenge were included in this study. Clinical H/O and other interventions were evaluated. Results: Among 8 patients, 6 (75%) were children and 2 (25%) were adults. There was an equal male-female distribution. Serum creatinine level was within the normal limit in six patients (75%), and elevated in two patients (25%). USG of renal system revealed mild HDN with PUJO in 03 (37.5%) patients, moderate HDN with PUJO in 02 (25%), gross HDN with PUJO in 1 (12.5%), extra renal pelvis in 01 (12.5%), and normal findings in 01 (12.5%) patients. Baseline diuretic DTPA renograms showed bilateral Homsy.s sign in 1 and unilateral in 7 patients. Among 7 patients, 6 positive Homsy.s signs were in the right kidney and 01 in the left kidney. Normal parenchymal function was found in 07, and mild parenchymal impairment was found in 02 affected patients. Conclusion: Surgical treatment is recommended for intermittent types of PUJO, as eventually it leads to frank obstruction and impairment of renal function. To confirm diagnosis, the F-15 diuretic protocol is recommended, where the maximum diuretic effect can result in either an obstructive or non-obstructive pattern of the curve. Bangladesh J. Nuclear Med. 27(1): 21-33, 2024